Răspuns :
[tex]\it a)\ (-13-26):13=(-39):13=-3\\ \\ a')\ (-13-26):13=-13:13-26:13=-1-2=-3[/tex]
[tex]\it b)\ (56-35):(-7)=21:(-7)=-3\\ \\ b')\ (56-35):(-7)=56:(-7)-35:(-7)=-8+5=-3[/tex]
[tex]\it c)\ (-7777+77):(-77)=-7700:(-77)=100\\ \\ c')\ (-7777+77):(-77)=-7777:(-77)+77:(-77)=101-1=100[/tex]
[tex](-7777+77):(-77)=-7700:(-77)=\dfrac{-7777+77}{-77}=\dfrac{-77(101-1)}{-77}=100[/tex]
Răspuns:
Explicație pas cu pas:
a) ( - 13 - 26 ) : 13 =( - 39 ) : 13 = - 3 → primul mod
= ( - 13 ) : 13 - ( 26 : 13 ) = - 1 - 2 = - 3 → al doilea mod
________________________________________________
b) ( 56 - 35 ) : ( - 7 ) = 21 : ( - 7 ) = - 3 → primul mod
= 56 : ( - 7 ) - 35 : ( - 7 ) = - 8 + 5 = - 3 → al doilea mod
_________________________________________
c) ( -7777 + 77 ) : ( - 77 ) = ( -7700) : ( -77) = 100 → primul mod
= ( -7777) : ( -77) + 77 : ( -77) = 101 - 1 = 100 → al doilea mod